The Impact of Participation in Educational Programs on Elderly’s Life Satisfaction - Bora Jin (Adult Education Research Conference, 2017)
This study explored impact of the participation in educational programs on elderly’s life satisfaction. Semi-structured interviews were conducted. It showed that participation in educational programs has positively impacted the elderly.
Keywords: Educational programs; Elderly; Life Satisfaction.